The Review of the Effectiveness of Celebrity Advertising that Influence Consumeras Perception and Buying Behavior (Global Journal of Management and Business Research, 2015)
This paper intends to appraise and understand celebrity advertising and its effectiveness. By deeply examining and addressing the components of celebrity advertising, the advantages and disadvantages associated with it, and the elements of successful and unsuccessful implementations, it will be clear that with a compelling and logical celebrity-brand fit, the application of celebrities as brand advocates can be used to a company's competitive advantage.
Keywords: celebrity advertising; consumer#x2019; s perception; effectiveness; buying behavior